2022
DOI: 10.1155/2022/3665617
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation-Related Genes Predict the Prognosis and Immune Fraction of Ovarian Cancer Patients Based on Weighted Gene Coexpression Network Analysis (WGCNA) and Machine Learning

Abstract: Background. Ovarian cancer (OC) is a malignancy exhibiting high mortality in female tumors. Glycosylation is a posttranslational modification of proteins but research has failed to demonstrate a systematic link between glycosylation-related signatures and tumor environment of OC. Purpose. This study is aimed at developing a novel model with glycosylation-related messenger RNAs (GRmRNAs) to predict the prognosis and immune function in OC patients. Methods. The transcriptional profiles and clinical phenotypes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…As a result of tumor mutations, new antigens are produced, and the exposure of these antigens may provide new targeting opportunities for immunotherapy. For instance, Zhao et al developed a model incorporating 4 GT genes, ALG8, DCTN4, DCTN6, and UBB, to predict ovarian cancer (OC) patients and immune function [23]. The results showed that high-risk patients were at higher risk compared to low-risk patients, and tumor purity together with tumor mutational load was negatively correlated with risk scores.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of tumor mutations, new antigens are produced, and the exposure of these antigens may provide new targeting opportunities for immunotherapy. For instance, Zhao et al developed a model incorporating 4 GT genes, ALG8, DCTN4, DCTN6, and UBB, to predict ovarian cancer (OC) patients and immune function [23]. The results showed that high-risk patients were at higher risk compared to low-risk patients, and tumor purity together with tumor mutational load was negatively correlated with risk scores.…”
Section: Discussionmentioning
confidence: 99%
“…ALG8 is an alpha-1,3-glucosyltransferase and ALG8-CGD (congenital disorders of glycosylation) is a widely studied monogenic disorder of glycosylation that involves multisystem disorders [ 68 ]. In malignancies, ALG8 was a variate of a risk predictive model established for gastric cancer [ 69 ] and ovarian cancer [ 70 ]. However, consistent with Zhao et al’s study [ 70 ], ALG8 in our study was overexpressed in OC tissues and led to favourable outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In malignancies, ALG8 was a variate of a risk predictive model established for gastric cancer [ 69 ] and ovarian cancer [ 70 ]. However, consistent with Zhao et al’s study [ 70 ], ALG8 in our study was overexpressed in OC tissues and led to favourable outcomes. In summary, except for ALG8, other five GTs are all key enzymes that involves in the synthesis of cancer associated glycans and may exist a close tie between each other.…”
Section: Discussionmentioning
confidence: 99%
“… Yan et al (2020) constructed a prognostic feature model of ovarian cancer based on immune cell infiltration ( Yan et al, 2020 ). Zhao et al (2022) constructed a prognostic model of ovarian cancer through WGCNA and machine learning methods ( Zhao et al, 2022 ). However, there is no research to analyze the diagnostic signature genes of ovarian cancer through machine learning algorithms and medical big data.…”
Section: Discussionmentioning
confidence: 99%